The Faces of Christmas - Onimisi, Emmanuel (USA, 2022)
The faces of Christmas shows us a glimpse into the Christmas Story, from the perpspectives of people involved in and affected by the coming of God as a man...
Keywords: Bible Story; Christmas; Juvenile Non-Fiction